2018
DOI: 10.5152/tjar.2018.46244
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Dexmedetomidine on Ileum and Kidney Damage Caused by Mesenchymal Ischaemia in Rats

Abstract: the manuscript, references should be cited using Arabic numbers in parentheses. The reference styles for different types of publications are presented in the following examples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In ischemia-reperfusion injury and oxidative stress studies with DEX it has been reported that DEX has a histopathological improvement effect and regression effect in damaged tissues of dif-ferent organs (29,30). In an experimental study, Sancaktar et al reported that there was a signifi cant decrease in renal apoptotic index in the DEX group compared to the I/R damage group (29). Again Chen et al showed that use of DEX reduces apoptosis in cardiopulmonary bypass related neuronal apoptosis (31).…”
Section: Discussionmentioning
confidence: 99%
“…In ischemia-reperfusion injury and oxidative stress studies with DEX it has been reported that DEX has a histopathological improvement effect and regression effect in damaged tissues of dif-ferent organs (29,30). In an experimental study, Sancaktar et al reported that there was a signifi cant decrease in renal apoptotic index in the DEX group compared to the I/R damage group (29). Again Chen et al showed that use of DEX reduces apoptosis in cardiopulmonary bypass related neuronal apoptosis (31).…”
Section: Discussionmentioning
confidence: 99%
“…9,10,15 This protection was conferred through multiple signalling molecules and pathways, including NF-κB, ERK1/2, Nrf2, JAK2/STAT3 and p38/NO, all of which are directly or indirectly regulated by α 2 -AR. However, a high concentration (50 nM) of Dex conversely promoted DDP-induced toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In most previous studies, Dex was found to confer protection against anti-cancer drugs, hypoxia and ischaemic/reperfusion injury in multiple cell lines. 9,10,15 This protection was conferred through multiple signalling molecules and pathways, including NF-κB, ERK1/2, Nrf2, JAK2/STAT3 and p38/NO, all of which are directly or indirectly regulated by α 2 -AR. Previous studies have reported that α 2 -AR-mediated inhibition of NF-κB is responsible for Dex protection against DDP toxicity in kidneys.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations